Bacterial Profile and Antimicrobial Resistance Patterns of Diabetic Foot Infections in a Major Research Hospital of Turkey - Belgin Coşkun; Müge Ayhan; Serap Ulusoy; Rahmet Guner (MDPI AG, 2024)
Background/Aim: Diabetic foot infection (DFI) occurs frequently in patients, followed up with diabetic foot ulcers (DFU). For this reason, antibiotic treatment is often used in patients followed with DFU. Inappropriate use of antibiotics and increasing antibiotic resistance threaten public health. We aimed to investigate the microbial spectrum and antimicrobial resistance patterns isolated from diabetic foot infections in Turkey and help clinicians to choose optimal antibiotics empirically. Materials and Methods: This study was planned as a retrospective, single-center, cross-sectional study. Two hundred sixty-two patients whose causative microorganism was isolated in culture of tissue between 1 January 2021 and 31 December 2022 were included in this study. Bacterial profile and antimicrobial resistance patterns were analyzed. Results: Four hundred thirty two isolates from 262 patients isolated in culture of tissue were evaluated. Of these microorganisms, 57.60% were Gram-negative, 41.20% were Gram-positive bacteria, and 1.2% were Candida spp. The most frequently detected Gram-positive microorganism was Staphylococcus spp. Gram-negative microorganisms were Escherichia coli (E. coli) and Pseudomonas aeruginosa (P. aeruginosa). Polymicrobial infections were observed in 40.5% of the patients. Methicillin-resistant Staphylococcus spp. rate was 51.3%, while extended-spectrum beta-lactamase (ESBL) resistance for E. coli was 66.7%. Conclusions: Due to increasing antibiotic resistance rates, treatment of common infections becomes more difficult. Knowledge of the microbiological profile and antibiotic resistance patterns of patients with DFIs is useful to guide empirical therapy.